In vitro model of hyaluronan synthase gene expression associated with lipopolysaccharide-induced inflammation in SW982 cell line - Nawarat Viriyakhasem (2018)
© 2014, The Society for In Vitro Biology. The present study aimed to demonstrate the phenomena of hyaluronan synthesis in response to lipopolysaccharide-induced inflammation in SW982, a human synovial sarcoma cell line. The expression of IL-1ß, including Toll-like receptor 4 and IL-1ß-converting enzyme, was proved to be induced by a reverse transcription-polymerase chain reaction. The expression of HAS genes encoding enzyme hyaluronan synthase 2 and 3, including CD44 gene which encodes the cell surface receptor of hyaluronan were upregulated in association with the activation of inflammation, along with an increase in hyaluronan level in the culture medium. The highest expression of HAS2 and HAS3 was found at 9 h after treatment with lipopolysaccharide. However, HAS1 gene expression was not detectable neither with the non-treatment nor with the treatment with lipopolysaccharide. Dexamethasone at 30 nM significantly suppressed lipopolysaccharide-induced HAS genes expression, leading to the decline of the hyaluronan level in the culture medium. Our results demonstrated the effective tool for studying hyaluronan synthesis in association with inflammation in the SW982 cell line.